Internationalizing Higher Education in Malaysia – Understanding, Practices and Challenges, by Tham Siew Yean (ed.) Singapore: Institute of Southeast Asian Studies (ISEAS), 2013, 139 pp. - Morshidi Sirat (Kajian Malaysia, 2013)
Nine well-known academics in the Malaysian higher education scene contributed seven chapters in this 147-page book. These nine academics with background ranging from sociology, economics and education have adopted a multidisciplinary style and approach to the analysis of internationalisation in Malaysia. While the authors are flirting with policy imperatives for internationalisation in Malaysia (on p. 9, the authors claimed that the book also aims to make policy recommendations), the book was not written from a policy perspective. On the contrary, the book was written from the perspective of academic discourse, raising issues relevant for policy rather than policy prescription. This is understandable as none of the authors have access to policy documents to provide policy context to their discussion and analysis. Admittedly, there are other considerations involved in policy prescriptions, and we must not naively assume that these will be purely based on empirical findings. Evidence-based policy does not happen quite often in policy formulation. This is very true in the case of higher education policy.